Study of response characteristics of cross-well induced polarization method in anisotropic media - Junke, Zhang; Lei, Zhou; Xinyu, Wang; Xingbing, Xie; Yurong, Mao; Liangjun, Yan (Frontiers in Earth Science, 2024)
The borehole induced polarization method has been widely used in deep mineral exploration, oil and gas resource exploration, and water resource exploration because of its high efficiency and good exploration effect. At present, the related research on the cross-well induced polarization method assumes that the underground medium is isotropic, but the electrical characteristics of the actual earth medium are anisotropic. To analyze the influence of the anisotropic characteristics on the cross-well induced polarization method, in this paper, the anisotropic forward algorithm of conductivity and polarizability in different principal axis directions based on the finite element method is studied. A three-dimensional forward simulation of the cross-well induced polarization method in anisotropic media is realized. The effectiveness and correctness of the algorithm are verified by testing and comparing complex 3-D isotropic and anisotropic models. Anisotropic geological models of the horizontal plate and inclined plate are constructed to analyze the anisotropic influences of conductivity and polarizability in different principal axis directions on the cross-well induced polarization response. The results show that the emitter sources with different depths in the well have different influences on the electrical response of the plates. Anisotropic conductivity and polarizability in horizontal plates exhibit most pronounced characteristics in the x-direction, significantly influencing the apparent polarizability curves. However, when the resistivity and polarizability are both anisotropic, the change in the z-direction is the most complicated. When the plate is inclined, the amplitude of the electrical response curve decreases to a certain extent, and the position where the amplitude appears shifts to different degrees. Notably, the response curves of the y-direction anisotropy are basically consistent with the response curves of the isotropy, regardless of the anisotropy of the conductivity and polarizability or anomalous body tilts. The results of this study improve our understanding of the influence of anisotropy on cross-well induced polarization and provide theoretical support for the interpretation of cross-well induced polarization data considering anisotropy.